Rent a home: a cross platform mobile application to list and search rental homes - Ali, Yusuf (Kansas State University, 2016)
Finding a desired off-campus home could be a difficult task for incoming students at K-State. This cross platform mobile application can help students in this task. This mobile application will serve as platform for students and home owners to find, list and review a property. Users can create their personal account and manage their profile and properties they listed. They can post multiple property listings with the key details and these listings will be visible to all the other users. To avoid spam and repetitive postings there is an address verification system in place. While posting a property listing the address is verified with Google maps database. If Google maps fail to identify the address or if that address is already listed, the user will not be allowed to list that property. Users can see all the property listings and their details including a Google map location image, a link to navigate to the address, contact details of the owner, reviews of other users. Users can rate a property from 1(low) to 5(high) along with an optional review. The review and rating can help other user to select a desired place to live. The user interface is developed with web technologies and using Cordova the same code can be used to convert it into a mobile application for both iOS and Android which makes this application platform independent and easily available.
Keywords: Mobile app; Android app; Computer science